The Correlation Between Anxiety and Smartphone Addiction Among Medical Students - Femmy T. Fahira; Sulistiawati; Azimatul Karimah (Faculty of Medicine, Universitas Airlangga, 2023)
Introductions: Various studies showed that medical students were more prone to exposure to stress and anxiety than their peers. Along with the rising popularity of smartphones, university students tend to spend time on smartphones to distract themselves from stress. However, the overuse of smartphones may lead to addiction. Methods: This study applied a modified version of the Smartphone Addiction Scale (SAS) to assess the level of addiction and Zung's Self-Rating Anxiety Scale (ZSAS) to quantify the severity of anxiety. Based on Spearman's rho statistical test, the value of p = 0.000 and r = 0.297. Results: There are 374 preclinical students included in this study. Most students (47.06%) use smartphones 5-10 hours daily. The majority of students were having mild anxiety (54.81%), followed by moderate anxiety (39.84%) and severe anxiety (5.35%). The results showed that smartphone addiction relates significantly to students' anxiety (p<0.05). Conclusions: From this study, it can be concluded that there is a positive and signiaficant correlation between anxiety and smartphone addiction among preclinical students in the Faculty of Medicine, Universitas Airlangga.